Diverse knowledge exploration and diffusion in MNCs - Berry, Heather (Strategic Management Journal, 2023)
Abstract Research Summary This article examines the influence that intra‐firm manufacturing linkages have on knowledge exploration outcomes in foreign subsidiaries. Although it is common to focus on the importance of keeping exploratory units separate from other firm operations to encourage a more diverse range of solutions, I explore the role that strong manufacturing outflows play in encouraging both the search for diverse knowledge and the diffusion of that knowledge across multinational corporation (MNC) operations. Empirical results from a comprehensive panel of US MNCs merged with the Derwent worldwide patent data reveal that foreign exploratory units with strong intra‐firm manufacturing outflows are more likely to include new‐to‐the‐MNC technology domains in their innovations and that these diverse innovations are more likely to diffuse out of units that have strong intra‐firm manufacturing outflows. Managerial Summary Although foreign exploratory units can provide MNCs with opportunities to tap into diverse knowledge clusters to enhance the competitiveness of a firm, many studies report firm biases against new and unfamiliar knowledge that has been generated in foreign operations. This article explores the role that manufacturing linkages play in providing visible signals of local operation competencies to the rest of an MNC, helping to overcome biases against new and unproven technology domains and enabling foreign exploratory units to pursue diverse, local knowledge inputs and specialization for the MNC. The empirical results confirm that foreign exploratory units that manufacture inputs and products for other MNC operations are more likely to use new‐to‐the‐MNC technology domains in their innovations than foreign exploratory units without such linkages.